Microstructural Evolution During the Infiltration Treatment of Titanium CarbideIron Composite - Chae, K.W.; Chun, D.I.; Kim, D.Y.; Baik, Y.J.; Eun, K.Y. (1990)
The microstructural evolution of grainmatrix interfaces in TiCFe cermet has been observed and explained in terms of equilibration reaction and interfacial energy minimization. The coherency strain energy is assumed to be the driving force for enhanced dissolution of certain specific planes, which results in a very irregular grain shape. The equilibrium shape appears after heat treatment for a long period. Copyright ？ 1990, Wiley Blackwell. All rights reserved
Keywords: Composite Materials--Grain Size and Shape; Powder Metallurgy--Titanium; Cermets; Grain Evolution; Metallic Matrix; Titanium Carbide